Mineral Oil Aspiration Related Juvenile Idiopathic Arthritis - Andrew D. Nelson; Philip R. Fischer; Ann M. Reed; Mark E. Wylam (Case Reports in Pulmonology)
We describe the development of rheumatoid factor-positive migratory polyarthritis in a 5-year-old male who had been administered bidaily oral mineral oil as a laxative since birth. Minor respiratory symptoms, radiographic and bronchoscopic findings were consistent with chronic lipoid pneumonia. We speculate that immune sensitization to mineral oil promoted the clinical syndrome of juvenile idiopathic arthritis.